2018
DOI: 10.1093/cid/cix1142
|View full text |Cite
|
Sign up to set email alerts
|

Late Presentation With HIV in Africa: Phenotypes, Risk, and Risk Stratification in the REALITY Trial

Abstract: BackgroundSeverely immunocompromised human immunodeficiency virus (HIV)–infected individuals have high mortality shortly after starting antiretroviral therapy (ART). We investigated predictors of early mortality and “late presenter” phenotypes.MethodsThe Reduction of EArly MortaLITY (REALITY) trial enrolled ART-naive adults and children ≥5 years of age with CD4 counts <100 cells/µL initiating ART in Uganda, Zimbabwe, Malawi, and Kenya. Baseline predictors of mortality through 48 weeks were identified using Cox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 13 publications
3
32
1
Order By: Relevance
“…Among HIV‐associated medical admissions in Cape Town, South Africa, 5% of patients died in hospital and at 90 days, 13% had died 2 . A recent randomised‐controlled trial, which aimed to assess reduction in early mortality through enhanced anti‐infective prophylaxis and was conducted in four sub‐Saharan African countries, reported 12% mortality at 48 weeks after ART initiation among participants with very advanced HIV disease (CD4 count < 100 cells/µL) 8 . The low median CD4 count and high median HIV viral load among enrolled patients in this study indicated severe immunodeficiency at admission and a poor baseline prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among HIV‐associated medical admissions in Cape Town, South Africa, 5% of patients died in hospital and at 90 days, 13% had died 2 . A recent randomised‐controlled trial, which aimed to assess reduction in early mortality through enhanced anti‐infective prophylaxis and was conducted in four sub‐Saharan African countries, reported 12% mortality at 48 weeks after ART initiation among participants with very advanced HIV disease (CD4 count < 100 cells/µL) 8 . The low median CD4 count and high median HIV viral load among enrolled patients in this study indicated severe immunodeficiency at admission and a poor baseline prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…This large burden of advanced HIV disease translates to an increased risk of AIDS‐related opportunistic infections diagnosed in hospital, with a higher risk of death at lower CD4 counts 8 . Tuberculosis (TB), cryptococcal meningitis, Pneumocystis jirovecii pneumonia (PCP) and other invasive mycoses manifest as AIDS‐defining illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the pattern of OIs within PLHIV starting ART in today’s resource-limited setting may change compared to our cohort. However, no increase of CD4 cell counts at ART start was observed in sub-Saharan Africa after 2009, when the CD4 threshold for ART eligibility was raised from 200 to 350 cells/μL [ 21 ], and substantial proportions of patients continue to present with advanced disease in this setting [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mortality rates were highest during the first 4 weeks on ART. In this trial, patients at highest mortality risk had a high burden of symptoms, weight loss, poor mobility, and low albumin and hemoglobin level [ 9 ]. The second study, from Kenya and DRC, reported that tuberculosis, malaria, cryptococcal meningitis, and pneumonia were the main causes of death among HIV-infected hospitalized patients.…”
mentioning
confidence: 99%